Does occupational deregulation affect in-company vocational training? – Evidence from the 2004 Reform of the German Trade and Crafts Code - Petrik Runst; Jörg Thomä (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2018)
The European Commission actively evaluates occupational entry restrictions in all member states. This has attracted a growing interest among scholars of the German crafts sector as it is governed by an idiosyncratic national set of rules. We estimate the effects of the deregulation of the German Trade and Crafts Code in 2004 on the overall vocational training levels in affected crafts trades. We employ Difference-in-Differences regressions as well as Synthetic Control Methods on data for the entire population of the German crafts sector. We show that the overall effect of the reform on vocational training levels was negative, and is largely driven by the additional costs of obtaining a training license in the deregulated sector.
Keywords: D45; K20; L51; 330; Regulation; Impact analysis; vocational training; Craftsmanship